Analysis of a Decision Support System for Selecting the Best Gaming Smartphone Using the Simple Additive Weighting (SAW) Method - Kevin Gray Dasmasela; Wahit Desta Prastowo (novamindpress, 2026)
The rapid development of mobile hardware continues to reshape the performance landscape of gaming smartphones. Users increasingly require devices that balance high processing capability, thermal stability, display responsiveness, and price affordability. This study evaluates five gaming smartphones released in 2025 using the Simple Additive Weighting (SAW) method to determine the best performance-to-price option. The analysis considers five key criteria: benchmark performance, battery capacity, refresh rate, cooling system, and price. Each device is scored using normalized and weighted values to compute a final preference ranking. The findings show that the RedMagic 10 Pro achieves the highest score due to its strong performance metrics, advanced cooling system, and competitive pricing, making it the most balanced gaming smartphone in this comparison. The ROG Phone 9 Pro follows in second place, offering superior hardware but at a higher cost. Meanwhile, the RedMagic 10 Air emerges as a strong budget alternative, outperforming premium flagship phones in value-based analysis. This study demonstrates that multi-criteria decision-making provides clearer and more objective insights for consumers compared to single-parameter comparisons.